(untitled) (Jurnal Bahasa, 2010)
This article discusses the extent to which native Malay speakers from two cities, Kuching and Kota Bharu, accommodate the national standard accent. Kuching is chosen based on its geographical location, separated as it is from the centre of Malaysian administration in Peninsular Malaysia, while Kota Bharu is chosen based on the nature of the local dialect spoken by its residents. The study focuses on two significant phonological variables, namely open-ended (a), such as in kereta (car) and close-ended (r), such as in pasar (market). The level of accomodation of the national standard accent is examined based on different styles of speech and on two non-linguistic variables, namely age group and gender of the informant, in formal situations taking into account regional and local factors. Furthermore, the level of accomodation of the national standard accent is related to integration and identity issues - nationally or locally. Keywords: accent, accommodation, native speaker, style of speech, phonological variables, identity